Features of the scattering of polarized light by biological materials of fish - Arkhelyuk, Aleksandr; Pidkamin, Leonid; Khudyi, Oleksii; Marchenko, Mykhailo; Khuda, Lidiia; Kapusta, Andrzej; Ushenko, Alexander G.; Dubolazov, Alexander; Motrich, Artem; Tarnovetska, Maryna (My University, 2021)
The article presents the results of a study of the regularities of the scattering of polarized light by fish mucus and fish scales in order to identify matrix elements that are most sensitive to changes in the conformation, shape and size of protein macromolecules of fish mucus, and identify the structural features of the fish scales.
Keywords: polarized light; fish mucus; fish scale